e-Management - (3EjGf(B, (3OhOLs ((3GdbGgQI(B:s (3OGQ GdaLQ(B,s, 2006)
(3JYQja GdCYeGd GdJLGQjI GdEdjcJQhfjI heVGejfgG hcja JDKQ (Be-Business(3Ydi eOjQ (BIT (3hJbOje fehPL ddCYeGd GdJLGQjI GdEdjcJQhfjIs
Keywords: (3GdCYeGd GdJLGQjI GdEdcJQhfjI,(Be-Busines(3,eOjQ(BITs